Computational Thinking in Preschoolers - Ccanto, Florencio Flores; Vargas, Isabel Menacho; Acero-Zapaza, Ines Miryan; Zamata-Choque, Hugo Walter; Morales, Lourdes Galvez; Meza-Chaupis, Yeferzon; Flores-Lira, Jhoseline Gianella (Journal of Posthumanism, 2025)
The article explores the integration of computational thinking into early childhood education, aiming to evaluate how this approach can be implemented from the earliest stages of learning. The research employed a qualitative methodology based on a literature review, analyzing 17 studies published between 2015 and 2024, sourced from journals indexed in Scielo, SCOPUS, and Google Scholar. The reviewed studies focused on teaching strategies and technological tools applied in the preschool context. The findings indicate that computational thinking, encompassing skills such as sequencing, logic, and problem-solving, is essential for the holistic development of children in a digital environment. The tools and methodologies used have proven effective in introducing these concepts at an early age. However, the importance of adapting educational strategies to cultural and contextual specifics to optimize their effectiveness is highlighted. In conclusion, the early integration of computational thinking in preschool education facilitates a structured and creative way of thinking, which is fundamental for learning across various disciplines. Innovative strategies and the appropriate use of technology can transform early childhood education by fostering cognitive and creative skills. Continued research and development of educational approaches that adapt to different cultural contexts are necessary to better prepare students for the challenges of a digital and globalized future.